COGNITIVE-BEHAVIORAL THERAPY: AN ALLY OF THE UNIFIED HEALTH SYSTEM - Nunes, Rafael Zaneripe de Souza; Tuon, Lisiane; Souza, Rosimeri Vieira da Cruz de; Gomes, Karin Martins (Amadeus International Multidisciplinary Journal, 2020)
Abstract: The Unified Health System goes through several challenges, including the crisis related to public financing. The consequences generated by this crisis also affect the mental health network, which proves to be one of the most fragile networks in the public health system. As a result of the barriers encountered, this article seeks to analyze in the scientific literature how Cognitive-Behavioral Therapy can contribute to the better use of public spending through its objective and brief techniques. The study is characterized by a qualitative approach carried out through a non-systematic literature review in the data sources SCIELO, BVS, PUBMED® and Google Scholar. Although the number of articles found in the national literature is limited, studies conducted outside the country demonstrate the effectiveness of CBT in public health systems, especially regarding the remission of users' symptoms and the cost-benefit of public spending. Keywords: Cognitive Behavioral Therapy; Public Health; Unified Health System; Government Financing.